2009
DOI: 10.1111/j.1365-313x.2008.03707.x
|View full text |Cite
|
Sign up to set email alerts
|

OsGSR1 is involved in crosstalk between gibberellins and brassinosteroids in rice

Abstract: SummaryGibberellins (GAs) and brassinosteroids (BRs), two growth-promoting phytohormones, regulate many common physiological processes. Their interactions at the molecular level remain unclear. Here, we demonstrate that OsGSR1, a member of the GAST (GA-stimulated transcript) gene family, is induced by GA and repressed by BR. RNA interference (RNAi) transgenic rice plants with reduced OsGSR1 expression show phenotypes similar to plants deficient in BR, including short primary roots, erect leaves and reduced fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
173
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(175 citation statements)
references
References 57 publications
1
173
0
1
Order By: Relevance
“…To obtain a more comprehensive overview on monocot GSL genes, the rice genome was also searched for RSI1 homologs as a reference. This led to the identification of six novel gene family members in addition to the previously published genes OsGSR1 (Wang et al, 2009), OsGASR1, and OsGASR2 (Furukawa et al, 2006; Table I). The novel rice genes were numbered according to their closest maize relatives (OsGSL1, OsGSL5, OsGSL7, OsGSL8, and OsGSL9) or in one instance, when no maize ortholog was available, according to the closest Arabidopsis relative (OsGSL12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain a more comprehensive overview on monocot GSL genes, the rice genome was also searched for RSI1 homologs as a reference. This led to the identification of six novel gene family members in addition to the previously published genes OsGSR1 (Wang et al, 2009), OsGASR1, and OsGASR2 (Furukawa et al, 2006; Table I). The novel rice genes were numbered according to their closest maize relatives (OsGSL1, OsGSL5, OsGSL7, OsGSL8, and OsGSL9) or in one instance, when no maize ortholog was available, according to the closest Arabidopsis relative (OsGSL12).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the newly identified maize GASTlike genes ZmGSL1 to ZmGSL10, six novel rice genes were identified, bringing the total number of GASA/ GAST-like members from rice to nine. Phylogenetic reconstructions involving the previously identified rice (Furukawa et al, 2006;Wang et al, 2009), tomato (Shi et al, 1992;Taylor and Scheuring, 1994), and Arabidopsis (Roxrud et al, 2007) full-length GASTlike protein sequences grouped the newly identified monocot members into three distinct phylogenetic clades. The comparison of monocot and dicot GASA/GAST-like proteins in our study therefore reveals that during evolution eudicot members of the GASA/GAST-like family have developed along three different directions.…”
Section: Ga 3 Induces Expression Of Zmgsl Genesmentioning
confidence: 99%
“…24 Rice OsGSR1 gene expression is inhibited by GA and induced by BR. 14 And the AtGASA4 and AtGASA6 are ingeneral up regulated by growth hormones (auxin, BR, cytokinin, and GA) and down regulated by stresshormones (ABA, JA, and SA). 40 These results suggesting that the GASA gene family may be involved in a wide range of plant hormone signal transduction network.…”
Section: Gasa Proteins Subcellular Localizationmentioning
confidence: 99%
“…39 Normally, GASA proteins form 5 or 6 disulfide bonds and these disulfide bonds may be necessary for the senior structural of GASA and be critical for the GASA protein interactions with other proteins. 12,18 GASA protein participate in the regulation of plant growth and development upon interacting with different proteins, such as rice OsGSR1 is involved in the regulation of GA and BR crosstalk through interaction with BR (brassinosteroid) synthase DIM / DWF1 protein; 14 Potato Snakin-1 protein can interact with itself to play role in in the regulating cell division of potato leaf (Nahirnak et al, 2012). 32 …”
Section: Structure Of Gasa Proteinsmentioning
confidence: 99%
See 1 more Smart Citation